Pediatric myelin oligodendrocyte glycoprotein antibody-associated disease in southern China: analysis of 93 cases - Li, Xiaojing; Wu, Wenlin; Hou, Chi; Zeng, Yiru; Wu, Wenxiao; Chen, Lianfeng; Liao, Yinting; Zhu, Haixia; Tian, Yang; Peng, Bingwei; Zheng, Kelu; Shi, Kaili; et al. (Frontiers in Immunology, 2023)
Objective: To study the clinical features of children diagnosed with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) in southern China. Methods: Clinical data of children diagnosed with MOGAD from April 2014 to September 2021 were analyzed. Results: A total of 93 children (M/F=45/48; median onset age=6.0 y) with MOGAD were involved. Seizures or limb paralysis was the most common onset or course symptom, respectively. The most common lesion locations in brain MRI, orbital MRI and spinal cord MRI were basal ganglia and subcortical white matter, orbital segment of optic nerve and cervical segment, respectively. ADEM (58.10%) was the most common clinical phenotype. The relapse rate was 24.7%. Compared with the patients without relapse, relapsed had longer interval from onset to diagnosis (median: 19 days VS 20 days) and higher MOG antibody titer at onset (median: 1:32 VS 1:100) with longer positively persistent (median: 3 months VS 24 months). All patients received IVMP plus IVIG at acute phase, and 96.8% of patients achieved remission after one to three courses treatment. MMF, monthly IVIG and maintaining a low dose of oral prednisone were used alone or combination as maintenance immunotherapy for relapsed patients and effectively reduced relapse. 41.9% of patients had neurological sequelae, with movement disorder being the most commonly. Compared with patients without sequelae, patients with sequelae had higher MOG antibody titer at onset (median: 1:32 VS 1:100) with longer persistence (median: 3 months VS 6 months) and higher disease relapse rate (14.8% VS 38.5%). Conclusions: Of pediatric MOGAD in southern China: the median onset age was 6.0 years, with no obvious sex distribution difference; seizure or limb paralysis, respectively, being the most common onset or course symptom; the lesions of basal ganglia, subcortical white matter, the orbital segment of the optic nerve, and cervical segment were commonly involved in the CNS MRI; ADEM was the most common clinical phenotype; most had a good response to immunotherapy; although the relapse rate was relatively high, MMF, monthly IVIG and low dose of oral prednisone might effectively reduce relapse; neurological sequelae were not less seen possibly associated with MOG antibody status and disease relapse.